Pandemic's VAT Revenue: Inflation, Exchange Rates, and Population Challenges: Dilema Pajak di Tengah Pandemi: Dampak Inflasi, Nilai Tukar, dan Populasi terhadap Pendapatan PPN - Linna Wulandari; Imelda Dian Rahmawati (Academia Open, 2023)
This quantitative study investigates the impact of inflation, exchange rates, and population on Value Added Tax (VAT) revenue during the Covid-19 pandemic, specifically focusing on the Kpp Sidoarjo Selatan Regional Office. By employing a time series analysis spanning 36 observations from 2018 to 2020, this research employs a non-probability saturated sampling technique. The data analysis is conducted using Multiple Linear Regression with SPSS 26. The findings reveal that inflation, exchange rates, and population significantly influence VAT receipts during the pandemic. Consequently, these results shed light on the challenges faced by tax authorities and offer implications for policymakers, taxpayers, and economists alike. Highlights: Impact of Inflation: Analyzing the influence of inflation on VAT revenue during the Covid-19 pandemic. Exchange Rate Effects: Examining how exchange rate fluctuations affect VAT receipts amidst the pandemic. Population Dynamics: Investigating the role of population changes in shaping VAT revenue during the Covid-19 crisis. Keywords: Inflation, Exchange Rates, Population, VAT Revenue, Covid-19 Pandemic